2011
DOI: 10.1007/s10858-011-9490-8
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolomics of mammalian cell and tissue cultures

Abstract: NMR spectroscopy was used to evaluate growth media and the cellular metabolome in two systems of interest to biomedical research. The first of these was a Chinese hamster ovary cell line engineered to express a recombinant protein. Here, NMR spectroscopy and a quantum mechanical total line shape analysis were utilized to quantify 30 metabolites such as amino acids, Krebs cycle intermediates, activated sugars, cofactors, and others in both media and cell extracts. The impact of bioreactor scale and addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…A CHO DG44 cell line expressing a recombinant antibody fusion protein was used for all experiments, and the cell line and process conditions were similar to those previously described . Cell cultures were expanded in a series of shake flasks, rocker bags, and seed bioreactors to generate enough cells to inoculate production bioreactors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A CHO DG44 cell line expressing a recombinant antibody fusion protein was used for all experiments, and the cell line and process conditions were similar to those previously described . Cell cultures were expanded in a series of shake flasks, rocker bags, and seed bioreactors to generate enough cells to inoculate production bioreactors.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, advances in high‐throughput technologies and robotics are driving bioprocess development to even smaller, milliliter scale . Yet, it is known that productivity is generally lower in large (kL) production relative to small (L or less) reactor scales .…”
Section: Introductionmentioning
confidence: 99%
“…Both NMR [47,48] and mass spectrometry [49] based metabolomic techniques have been developed for this purpose. The effect of dextran sulfate, a commonly used anti-aggregation agent, and volume of the bioreactor were shown to impact specific media nutrients and cellular components [50] and recently, the biochemical reprogramming of two different variants of CHO cells by temperature shift has been reported [51]. This application of metabolomics avoids many of the pitfalls of studying whole animals, since there are fewer concurrent processes and nutrient influx and efflux can be more closely controlled and measured.…”
Section: Biologics Production Applicationsmentioning
confidence: 99%
“…These authors reported on the development of a methodology they termed ‘Fermentanomics’ to generate appropriate spectra whereby 50 components were identified [17]. A subsequent study by Aranibar et al used NMR to profile and quantify 30 key metabolites in a CHO cell line engineered to express a model fusion protein demonstrating that the metabolite measurements correlated with currently accepted endpoint based measures, validating the use of NMR for such an approach [18]. NMR has the advantage over other methods such as GC-MS in that labeling/derivatization of the metabolites is not required which reduces the time taken to process samples and in principle, measurements can be made in real time.…”
Section: Introductionmentioning
confidence: 99%